(untitled) (Panacea Journal of Medical Sciences, 2022)
Introduction: SARS-CoV-2 causing COVID 19 disease has emerged as one of the most infectious pathogen known to humans, causing severe acute respiratory illness (SARI) along with MERS and Influenza A/H1N1. The proportion of asymptomatic and mild illness is significantly higher and a minimal proportion of individuals develop a severe disease. Albeit, more cases of COVID-19 are from India, but the data regarding clinical epidemiology of COVID-19 in India is very low. In this backdrop, the present study was aimed to evaluate the clinical/epidemiological characteristics and outcomes of asymptomatic vs. symptomatic COVID-19 patients. Materials and Methods: All relevant clinical and demographic and epidemiological information was recorded over a period of one year From March 2020 to march 2021. A total of 217,665 samples from clinically suspected cases of COVID-19 were collected and using upper respiratory tract swabs. RT PCR assay was conducted according to the manufacturer’s instructions for the detection of RNA from SARS-CoV-2 present in the nasal pharyngeal swabs of from the patients suspected of COVID-19. Results: Out of the total 217,665 samples, 133474 (61.3%) were males and 84,191 (38.7%) were females. Among the 24,009 (11%) tested positive cases for SARS-CoV-2 infection, 15,254 (63.5%) were males and 8755 (36.5%) were females. The age group between 30 – 39 years showed high positivity and the fever was the most common symptom. Among the positive cases 60% were asymptomatic and 40% were symptomatic. Male patients, patients above 60 years of age and with comorbid conditions were more symptomatic. Children with <10> Conclusion: In our study, theproportion of asymptomatic COVID-19 was higher with male preponderance. Thus the higher number of asymptomatic positive patients with increased chance of transmission is missed on symptom-based screening calls for adherence to preventive measures. Thus, effective measures must be taken among the asymptomatic cases to halt the transmission of disease, prevent death and alter the course of this epidemic.